Local Power and Its Limits: Three Decades of Attempts to Revitalize Kitchener's CBD - Filion, Pierre; Bunting, Trudi (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1993)
This article which covers thirty years of central-area change in the City of Kitchener, Ontario focuses on the initial impetus that led to the preparation of large-scale plans, on the down-scaling and partial implementation of those plans, and on the current decision-making environment that allows for more public participation than existed in the past. The local political scene was dominated by a well-organized coalition of interest groups promoting urban renewal in the central business district, yet this coalition was unable to achieve its objectives. The situation is attributed to suburbanization and related shifts in political and economic power at the municipal level; the vulnerability of municipal administrations to senior governments' priority changes; tensions within the coalition itself; and the growing empowerment of other local groups unsympathetic to the coalition's goals. Generally, the emphasis is on limitations to the capacity of locally-powerful actors to implement large-scale and long-term policies in a consistent fashion.